Economic policy strategies in major industrial countries - Günter Großer; Günter Weinert (Intereconomics, 1983)
The stubborn weakness of growth in the industrial countries since the mid-seventies is a manifestation of a serious crisis of stabilisation and adjustment whose roots go far beyond the oil price increases. Against this background there was a marked turn in the direction of economic policy as a result of changes of government in 1979 in the United Kingdom and in 1981 in the USA and France. The programmes to stimulate economic growth were based on the supply-side concept in the UK and the USA but on the demand concept in France. Our article assesses the measures actually taken and the policy accent in the three countries against the background of previous economic developments and the prevailing political and institutional circumstances.
Keywords: 330